"Parenting Is Not a Job … It's a Relationship": Recognition and Relational Knowledge Among Parents of Gender Non-conforming Children. Issue 1 (2nd January 2016) - Pyne, Jake
ABSTRACT: Parents of gender non-conforming children encounter substantial conflict as they negotiate their children's "Otherness." For decades, a pathologizing service model has advocated clinical correction. In opposition, some parents adopt affirming stances toward their children. This study explored the knowledge underneath this stance, asking parents of gender non-conforming children how they know what they know. Analysis revealed a process of recognition and knowledge of the children's needs acquired through relationship. Drawing on political philosophy and psychoanalytic theory, I argue that the affirming approach to gender non-conforming children is a non-aggressive response to the "Other" and a justice-based parenting practice.